Effect of graphite filler on the physiochemical properties of graphite reinforced thermoset rooflite – unsaturated polyester resin composites - M. Karunakaran; Ravi Subban; A. Thangamani; Chinnaswamy Vijayakumar Thangavel (Chimica Techno Acta)
It is well known that many polymers are insulators with poor mechanical properties, which limit their use in fuel cell applications. Physicochemical properties of the polymers can be improved by adding conductive fillers. Carbon-based materials like graphite, which provides excellent mechanical strength and thermal conductivity to the polymer matrices, is of special interest because of its abundance, low cost and light weight when compared to other carbon allotropes. In the present work we describe the physicochemical properties of rooflite unsaturated polyester resin/graphite composites. Rooflite resin and three of its composites containing 1%, 3% and 5% of graphite by weight (C-2, C-3, and C-4, respectively) were synthesized and characterized by FTIR spectral data. XRD showed two peaks at 2q = 27.37°and 55.40° with d spacing value of 3.2559 nm and 1.6571 nm, respectively, indicating the change in degree of crystallinity of the composite. The calculated crystallinity for the resin is 7.3%, and for C-2, C-3 and C-4 its values are 12.1%, 14.3%, 17.1%, respectively, evidencing the interactions between the graphite and polymer matrix. The composites showed fractured surfaces and porous rough structure with randomly distributed vascularized cavities. Agglomeration occurs, when the concentration of graphite increases. The glass transition temperature for the pure resin is 65.9 °C and increases when the resin is filled with graphite. Thermogravimetric analysis (TGA) of the composites showed no marked difference between Tmax and Tfinal, and LOI values of C-3 and C-4 are above 21%, making them self-extinguishable materials that could be used for making bipolar plates. The chemical resistance investigation against water, NaCl, NaOH, acetic acid, and toluene showed more resistance to acid than alkali solutions. These rooflite resin/graphite composites could be further studied to explore the possibility of making bipolar plates, which are an essential component of fuel cells.